Mixed convection in the stagnation-point flow over a vertical stretching sheet in the presence of thermal radiation - Manjunatha, S.; Gireesha, B. J.; Bagewadi, Channabasappa Shanthappa (Zielona Góra: Uniwersytet Zielonogórski)
An unsteady two-dimensional stagnation-point mixed convection flow of a viscous, incompressible dusty fluid towards a vertical stretching sheet has been examined. The stretching velocity and the free stream velocity are assumed to vary linearly with the distance from the stagnation point. The problem is analyzed using similarity solutions. The similarity ordinary differential equations were then solved numerical by using the RKF-45 method. The effects of various physical parameters on the velocity profile and skin-friction coefficient are also discussed in this paper. Some important findings reported in this work reveal that the effect of radiation has a significant impact on controlling the rate of heat transfer in the boundary layer region.
Keywords: boundary layer flow; stretching porous surface; mixed convective parameter; thermal radiation; numerical solutions; dusty fluid; free stream velocity